Characterization of the Arabidopsis thaliana heme oxygenase 1 promoter in response to salinity, iron deficiency, and mercury exposure - F.-Q. Wang; J. Yang; C. Dai; M.-Z. Wu; Y.-H. Zhang; W.-B. Shen (Biologia Plantarum, 2017)
The Arabidopsis heme oxygenase 1 (HY1) plays a significant role in the signal transduction of abiotic stimuli and hormonal response. To characterize the HY1 promoter, an approximately 1.8 kb of it (pHY1, -1666 to +132) and its deletion fragments (5D1, -1528 to +132; 5D2, -1109 to +132; 5D3, -688 to +132; 5D4, -169 to +132; 3D1, -1666 to +100; 3D2, -1666 to -1; and 3D3, -1666 to -170), were fused to the β-glucuronidase (GUS) reporter gene and transformed into Arabidopsis. The transgenic plants were subjected to several environmental stimuli (especially to mild salinity, iron deficiency, and mercury exposure). The results show that the region from +1 to +100 in the 5'-untranslated region were essential for HY1 basal promoter activity. The induced GUS activities under NaCl and H2O2 treatments were slowed down by the progressive 5' deletion (from -1666 to -688) and correlated with the reduced numbers of myeloblastosis (MYB) binding sites (MBSs; -1542, -1333, -1078, and -177). The MBS-free promoter construct 5D4 (-169 to +132), however, fully lost the inducibility. Therefore, we propose that the MBS elements existing in the HY1 promoter might be crucial for salinity-induced HY1 up-regulation in an H2O2-dependent fashion. Moreover, the regions from -169 to -1 and -688 to -169 were presumed as the regulatory regions of HY1 promoter in response to iron deficiency and mercury exposure, respectively.